Production of Porcine Single Chain Variable Fragment (SCFV) selected against a recombinant fragment of Porcine Reproductive and Respiratory Syndrome virus non structural protein 2 - Koopman, Tammy L. (Kansas State University, 2011)
Over the last two decades molecular laboratory techniques have enabled researchers to investigate the infection, replication and pathogenesis of viral disease. In the early eighties, Dr. George Smith developed a unique system of molecular selection. He showed that the fd bacteriophage genome could be manipulated to carry a sequence of DNA coding for a protein not contained in the phage genome. Infection of the recombinant bacteriophage or phagemid into a specific strain of the bacterium, Escherichia coli, produced progeny phage with the coded protein displayed as a fusion with the phage's coat protein. Antibody phage display utilizes the same technology with the DNA encoding an antibody fragment. The DNA insert can carry the information to produce either a single chain variable fragment (scFv) producing the heavy chain variable and light chain variable (VH-VL) portion or a Fab fragment which also contains the heavy chain constant 1 with the light chain constant (CH and CL) portion of an antibody. Screening an antibody phage display library has the possibility of producing an antibody not produced in the normal course of immune selection. This decade also saw the emergence of a viral disease affecting the porcine population. The Porcine Reproductive and Respiratory Syndrome virus (PRRSV) has been one of the most costly diseases affecting the pig producer. Molecular investigations found that PRRSV is a single, positive-stranded RNA virus which codes for five structural and 12-13 nonstructural proteins producing an enveloped, icosahedral virus. An interesting characteristic of PRRSV is the ability to produce infective progeny with genomic deletions, insertions and mutations within the nonstructural protein 2 (nsp2). With this knowledge, many researchers have produced marker vaccines containing fluorescent tags with the hope of developing a DIVA (Differentiate Infected from Vaccinated Animals) vaccine. In my Master‟s studies, I studied the techniques of antibody phage display technology and how to apply these methods to producing scFvs which recognize a recombinant PRRSV nsp2 fragment protein and the native protein during infection of MARC-145 cells.
Keywords: Phage display; Porcine reproductive and respiratory syndrome virus; Single chain variable fragment (scFv); M13 bacteriophage; Immunology (0982); Molecular Biology (0307); Virology (0720)